EFFECT OF WORK STRESS AND WORK ENVIRONMENT ON PERFORMANCE CASE STUDY ON EMPLOYEES PT ASKRINDO BRANCH LAMPUNG IN 2020 - Frida Amelia Pratiwi; Afdal Mazni; M Ihsan Dacholfany (Universitas Muhammadiyah Metro, 2021)
Being an important factor in the organization, human resources are the driving force of all activities. In achieving organizational goals, there is a need for synergy between employees. In this case, management can see the factors that affect company performance in the aspect of human resources. These factors include work stress and work environment. The purpose of this study was to see whether there is an effect of stress and work environment on employee performance at PT Askrindo Lampung Branch. The method used in this research is quantitative descriptive method. The research object is PT Askrindo Lampung Branch. The subjects in this study were employees of PT Askrindo Lampung Branch in 2020. The technique used data using interviews, observations and questionnaires. The analytical tool used is to use the T test and multiple Linear Regression with the SPSS20 application analyzer. The result of this study is a significant influence on the variable work stress on performance, with the artist the higher the stress, the lower the alias performance. In fact, the work environment variable has a significant positive effect on performance, which means that the better the work environment, the better the company's performance.